Catalytic composition for increasing yield of low-carbon olefins and light oil, preparation method of catalytic composition and hydrocarbon oil catalytic conversion method
By using a catalytic composition containing MFI molecular sieve, phosphorus-aluminum binder and porous silicon-aluminum composite material, the problem of increased propylene yield but decreased gasoline yield in the prior art is solved, efficient catalytic conversion of low-carbon olefins and light oils is achieved, and heavy oil cracking capacity and propylene selectivity are improved.
Patent Information
- Application Number
- CN202311435192.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-10-31
AI Technical Summary
While improving the propylene yield, the prior art leads to a decrease in gasoline yield and insufficient cracking capacity of heavy oil and propylene selectivity.
Provided is a catalytic composition with a high yield of low-carbon olefins and light oils, containing MFI molecular sieve, phosphorus-aluminum binder, porous silicon-aluminum composite material, other inorganic binders and clays, and improves the efficiency of catalytic cracking through synergistic action.
The yield of propylene is significantly improved, the total yield of gasoline and liquefied gas is high, the yield of coke is lower, and the total liquid yield and conversion rate are high, which improves heavy oil cracking capacity and propylene selectivity.
Smart Images

Figure CN119909731A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a catalytic composition for producing more low-carbon olefins and light oil, a preparation method thereof, and a method for catalytic conversion of hydrocarbon oil. Background Art
[0002] As a very important basic organic chemical raw material, the demand for propylene continues to grow. Catalytic cracking equipment has a wider source of raw materials and lower operating costs, making it more economical and convenient to increase the production of propylene. The acidity of the catalyst and the shape-selective effect of the pores determine the yield of low-carbon olefins in the product.
[0003] Prior art discloses a five-membered ring high-silicon zeolite catalyst for light olefins in a fluidized catalytic device, the catalyst comprising (a) a five-membered ring high-silicon zeolite, (b) 8-24 wt% of phosphorus, as P2O5, based on particles containing the five-membered ring high-silicon zeolite, 1-10 wt% of iron oxide, as Fe2O3, located outside the five-membered ring high-silicon zeolite skeleton. The catalyst is fluidizable and has an average particle size of about 20 to about 200 microns. The catalyst composition can increase the yield of light olefins such as propylene in a fluidized catalytic cracking (FCC) process, but while increasing propylene, it will reduce the gasoline yield. The prior art discloses a cracking aid for increasing the concentration of propylene, which, on a dry basis, consists of 10-65 wt% of a modified ZSM-5 molecular sieve, 0-60 wt% of clay, 15-60 wt% of an inorganic oxide binder, 0.5-15 wt% of a metal additive selected from one or more metals of Group VIIIB metals, and 2-25 wt% of a phosphorus additive, wherein the modified ZSM-5 molecular sieve is modified with phosphorus and a metal selected from one of Fe, Co or Ni, and its anhydrous chemical expression, calculated as oxide, is (0-0.3)Na2O·(0.5-5)Al2O3·(1.3-10)P2O5·(0.7-15)M x O y (70-97)SiO2, x represents the number of atoms of M, y represents a number required to satisfy the oxidation state of M, and the metal additive and phosphorus additive are both calculated as oxides. The cracking aid is applied to the catalytic cracking process of petroleum hydrocarbons, and can significantly increase the propylene concentration in the liquefied gas while increasing the yield of catalytic cracking liquefied gas and the octane number of catalytic cracking gasoline, but will significantly reduce the gasoline yield, while diesel and oil slurry will not be reduced. Summary of the invention
[0004] The purpose of the present invention is to provide a catalytic composition for producing more low-carbon olefins and light oil, a preparation method thereof, and a method for catalytic conversion of hydrocarbon oil. The catalytic composition of the present invention has a high propylene yield, and the light oil yield, that is, the total yield of gasoline and liquefied gas is high, the coke yield is lower, the total liquid yield and conversion rate are high, and the heavy oil cracking capacity and propylene olefin selectivity are significantly improved.
[0005] In order to achieve the above-mentioned object, the first aspect of the present disclosure provides a catalytic composition for producing more low-carbon olefins and light oil, wherein the catalytic composition contains MFI molecular sieve, phosphorus aluminum binder, porous silicon aluminum composite material, other inorganic binders and clay;
[0006] Based on the dry weight of the catalytic composition, the content of the MFI molecular sieve is 10-75% by weight, the content of the porous silicon-aluminum composite material is 1-30% by weight, the content of the phosphorus-aluminum binder is 3-35% by weight, the content of the other inorganic binder is 1-20% by weight, and the content of the clay is 0-60% by weight;
[0007] The total weight of the phosphorus-aluminum binder is taken as the basis, and the phosphorus-aluminum binder contains 3-15 weight % of Al2O3, 15-40 weight % of P2O5 and 0.1-10 weight % of a stabilizer; the phosphorus-aluminum binder has a P / Al weight ratio of 1.6-6, a pH value of 0.5-2.5, and a QP0 2 / QP0 0 1-5, where QP0 2 Indicated by 31 The chemical shift of the aluminum-phosphorus binder detected by P nuclear magnetic resonance spectroscopy is 12±2ppm, and the resonance signal peak area is QP0 0 Indicates the resonance signal peak area with a chemical shift of 0±2ppm; the average particle size of the phosphorus aluminum binder is 10-30nm;
[0008] The porous silicon-aluminum composite material has a mass composition of (0.01-1) Na2O: Al2O3: (2-5) SiO2 and a specific surface area of 300-600m 2 / g, the total pore volume is 0.15-0.4mL / g, and the volume of medium and large pores with a pore diameter of 2-50nm accounts for 20-40% of the total pore volume.
[0009] Optionally, the phosphorus-aluminum binder contains 3-12 wt% Al2O3, 15-32 wt% P2O5 and 0.5-5 wt% stabilizer; the phosphorus-aluminum binder has a P / Al weight ratio of 1.7-5.8, a pH value of 0.5-2.5, and a QP0 2 / QP0 0 The solid content of the phosphorus aluminum binder is 15-50% by weight.
[0010] Optionally, based on the dry weight of the catalytic composition, the content of the MFI molecular sieve is 15-65% by weight, the content of the porous silicon-aluminum composite material is 2-25% by weight, the content of the phosphorus-aluminum binder is 8-32% by weight, the content of the other inorganic binders is 2-20% by weight, and the content of the clay is 1-25% by weight.
[0011] Optionally, the other inorganic binder is one or more selected from pseudo-boehmite, acidified aluminum stone, aluminum sol, silica-alumina sol and silica sol;
[0012] The clay is selected from one or more of kaolin, sepiolite, attapulgite, rectorite, montmorillonite and diatomaceous earth;
[0013] The MFI molecular sieve is one or more selected from hydrogen-type MFI molecular sieve, phosphorus-containing MFI molecular sieve and transition metal-containing MFI molecular sieve.
[0014] The second aspect of the present disclosure provides a method for preparing the catalytic composition provided in the first aspect of the present disclosure, the method comprising:
[0015] S1, mixing the MFI molecular sieve, the porous silicon-aluminum composite material, the other inorganic binder, the clay and water, and controlling the pH value of the slurry to be greater than 2.5 to obtain a first slurry;
[0016] S2. After mixing the first slurry with the phosphorus aluminum binder, spray drying and calcining are performed to obtain the catalytic composition.
[0017] Optionally, the aluminum-phosphorus binder is prepared by a method comprising the following steps:
[0018] (1) mixing an aluminum source, water and a stabilizer at a temperature of 50-95° C. and stirring to obtain an aluminum oxide precursor solution having a solid content of 5-40% by weight;
[0019] (2) Mixing and reacting the alumina precursor solution with phosphate at a temperature of 25-70° C. and under stirring conditions to obtain the phosphate-aluminum binder.
[0020] Optionally, in step (1), the weight ratio of the aluminum source, water and stabilizer is 100:(50-800):(5-40), preferably 100:(100-750):(6-35), and the aluminum salt is calculated as aluminum oxide;
[0021] In step (2), the weight ratio of the aluminum oxide precursor solution to the phosphate is 100:(50-200), preferably 100:(60-150), and the phosphate is calculated as phosphorus oxide.
[0022] Optionally, the porous silicon-aluminum composite material is prepared by a method comprising the following steps:
[0023] (a) treating metakaolin obtained by calcining kaolin with an inorganic acid at 80-95° C. to obtain a first mixture;
[0024] (b) mixing the first mixture, sodium silicate, a directing agent and an alkaline solution to obtain a second mixture; wherein the second mixture has a composition of a weight ratio of (0.1-5) Na2O:Al2O3:(2-10)SiO2:(5-100)H2O;
[0025] (c) After subjecting the second mixture to hydrothermal crystallization treatment, the solid product is taken out, filtered and washed to obtain the porous silicon-aluminum composite material.
[0026] Optionally, in step (a), the weight ratio of the inorganic acid to the metakaolin is (0.01-0.1):1, wherein the inorganic acid is H + The metakaolin is measured by dry basis weight;
[0027] The weight ratio of the directing agent to the metakaolin is (0.01-1.0):1, and the directing agent is calculated on a dry basis of oxide.
[0028] Optionally, the aluminum source is selected from one or more of aluminum nitrate, aluminum sulfate and aluminum chloride;
[0029] The phosphate is diammonium hydrogen phosphate and / or ammonium dihydrogen phosphate;
[0030] The stabilizer is selected from one or more of acetic acid, glycolic acid, oxalic acid, malonic acid, malic acid, tartaric acid, succinic acid, adipic acid, maleic acid, itaconic acid and citric acid, preferably acetic acid or citric acid.
[0031] A third aspect of the present disclosure provides a method for catalytic conversion of hydrocarbon oil, the method comprising: contacting the hydrocarbon oil with a catalyst for reaction, wherein the catalyst contains the catalytic composition provided by the first aspect of the present disclosure.
[0032] Optionally, the reaction conditions include: temperature of 400-700°C, weight hourly space velocity of 8-120 hours -1 , the agent-oil weight ratio is 1-20.
[0033] Through the above technical scheme, the phosphorus aluminum binder in the catalytic composition disclosed herein works synergistically with the porous silicon aluminum composite material and the MFI molecular sieve, so that the catalytic composition can increase the yield of propylene, the total yield of gasoline and liquefied gas is high, the coke yield is lower, the total liquid yield and conversion rate are high, and the heavy oil cracking capacity and propene selectivity are significantly improved. The catalyst composition can be used as a main agent in catalytic cracking reactions to produce more light olefins, and can also be used as an auxiliary agent in catalytic cracking and catalytic cracking reactions to produce more light olefins.
[0034] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0036] Figure 1 It is the nuclear magnetic resonance spectrum of the phosphate aluminum binder prepared in Example 1 of the present disclosure and the nuclear magnetic resonance spectrum of the phosphate aluminum binder prepared in Comparative Example 1. DETAILED DESCRIPTION
[0037] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.
[0038] The first aspect of the present disclosure provides a catalytic composition for producing more low-carbon olefins and light oil, the catalytic composition comprising MFI molecular sieve, phosphorus aluminum binder, porous silicon aluminum composite material, other inorganic binders and clay;
[0039] Based on the dry weight of the catalytic composition, the content of the MFI molecular sieve is 10-75% by weight, the content of the porous silicon-aluminum composite material is 1-30% by weight, the content of the phosphorus-aluminum binder is 3-35% by weight, the content of the other inorganic binder is 1-20% by weight, and the content of the clay is 0-60% by weight;
[0040] The total weight of the phosphorus-aluminum binder is taken as the basis, and the phosphorus-aluminum binder contains 3-15 weight % of Al2O3, 15-40 weight % of P2O5 and 0.1-10 weight % of a stabilizer; the phosphorus-aluminum binder has a P / Al weight ratio of 1.6-6, a pH value of 0.5-2.5, and a QP0 2 / QP0 0 1-5, where QP0 2 Indicated by 31 The chemical shift of the aluminum-phosphorus binder detected by P nuclear magnetic resonance spectroscopy is 12±2ppm, and the resonance signal peak area is QP0 0 Indicates the resonance signal peak area with a chemical shift of 0±2ppm; the average particle size of the phosphorus aluminum binder is 10-30nm;
[0041] The porous silicon-aluminum composite material has a mass composition of (0.01-1) Na2O: Al2O3: (2-5) SiO2 and a specific surface area of 300-600m 2 / g, the total pore volume is 0.15-0.4mL / g, and the volume of medium and large pores with a pore diameter of 2-50nm accounts for 20-40% of the total pore volume.
[0042] The catalytic composition disclosed herein contains a phosphorus-aluminum binder, which has high acid density and activity, has better cracking ability and a longer service life. The porous silicon-aluminum composite material has abundant mesopores on the one hand to improve the diffusion of raw material molecules and reactants, and on the other hand to improve the activity of the matrix, which is conducive to the cracking of heavy oil molecules and improves propylene precursors. The phosphorus-aluminum binder synergizes with the porous silicon-aluminum composite material and the MFI molecular sieve, so that the catalytic composition can increase the yield of catalytic cracking liquefied gas and propylene, and the total yield of gasoline and liquefied gas is high, the coke yield is lower, the total liquid yield and conversion rate are high, and the heavy oil cracking ability and propene selectivity are significantly improved. The catalytic composition can be used as a main agent in a catalytic cracking reaction to produce more light olefins, and can also be used as an auxiliary agent in a catalytic cracking reaction to produce more light olefins.
[0043] According to the present disclosure, the average particle size of the phosphate-aluminum binder is detected by a transmission electron microscopy method, specifically, the phosphate-aluminum binder is subjected to a transmission electron microscopy analysis, 100 phosphate-aluminum binder particles are randomly selected from the TEM photo and their maximum diameters are respectively measured as their particle sizes, and the average value of the particle sizes of the 100 phosphate-aluminum binder particles is calculated, which is the average particle size.
[0044] According to the present disclosure, the specific surface area and pore volume are determined by the nitrogen adsorption method (GB / T5816-1995), RIPP151-90, "Determination of pore volume and pore size distribution of catalysts by nitrogen adsorption capacity method", see Yang Cuiding et al., ed., Petrochemical Analysis Methods, Science Press, 1990.
[0045] In a preferred embodiment of the present disclosure, the phosphorus-aluminum binder contains 3-12 wt% Al2O3, 15-32 wt% P2O5 and 0.5-5 wt% stabilizer; the phosphorus-aluminum binder has a P / Al weight ratio of 1.7-5.8, a pH value of 0.5-2.5, and a QP0 2 / QP0 0 The solid content of the phosphorus aluminum binder is 15-50% by weight.
[0046] In a specific embodiment of the present disclosure, based on the dry weight of the catalytic composition, the content of the MFI molecular sieve is 15-65% by weight, the content of the porous silicon-aluminum composite material is 2-25% by weight, the content of the phosphorus-aluminum binder is 8-32% by weight, the content of the other inorganic binders is 2-20% by weight, and the content of the clay is 1-25% by weight. Preferably, based on the dry weight of the catalytic composition, the content of the MFI molecular sieve is 20-60% by weight, the content of the porous silicon-aluminum composite material is 2-20% by weight, the content of the phosphorus-aluminum binder is 10-30% by weight, the content of the other inorganic binders is 10-18% by weight, and the content of the clay is 5-10% by weight.
[0047] According to the present disclosure, other inorganic binders can be commonly used by those skilled in the art in preparing catalysts. In a specific embodiment of the present disclosure, the other inorganic binder is one or more selected from pseudo-boehmite, diaspore, aluminum sol, silica-alumina sol and silica sol.
[0048] According to the present disclosure, the clay may be one or more of kaolin, sepiolite, attapulgite, rectorite, montmorillonite and diatomaceous earth.
[0049] In a specific embodiment of the present disclosure, the MFI molecular sieve is one or more selected from hydrogen-type MFI molecular sieve, phosphorus-containing MFI molecular sieve and transition metal-containing MFI molecular sieve.
[0050] The second aspect of the present disclosure provides a method for preparing the catalytic composition provided in the first aspect of the present disclosure, the method comprising: S1, mixing and slurrying the MFI molecular sieve, the porous silicon-aluminum composite material, the other inorganic binder, the clay and water, controlling the pH value of the slurry to be greater than 2.5, to obtain a first slurry; S2, mixing the first slurry with the phosphorus-aluminum binder, spray drying and calcining to obtain the catalytic composition.
[0051] The method disclosed in the present invention can prepare a catalytic composition with better catalytic performance. The catalytic composition can effectively improve the yield of light olefins (such as propylene), with a high total yield of gasoline and liquefied gas, a high total liquid yield, and a low coke yield, while promoting heavy oil conversion and reducing coke and oil slurry.
[0052] In a specific embodiment of the present disclosure, in step S1, the MFI molecular sieve, the porous silicon-aluminum composite material, the clay and water are first mixed and slurried, and then the other inorganic binder is added to the obtained mixture for mixing and slurrying to obtain the first slurry, which is beneficial to further improve the activity and strength of the catalytic composition.
[0053] According to the present disclosure, spray drying is a technical means well known to those skilled in the art, and the specific method is not repeated here. In a specific embodiment, the inlet temperature of spray drying can be 300-700°C, and the outlet temperature can be 80-200°C.
[0054] In a specific embodiment of the present disclosure, the calcination temperature is 400-700° C., preferably 450-600° C., and the calcination time is 0.5-100 hours, preferably 0.5-10 hours.
[0055] In a specific embodiment of the present disclosure, the phosphoaluminum binder is prepared by a method comprising the following steps: (1) mixing an aluminum source, water and a stabilizer at a temperature of 50-95°C and under stirring to obtain an alumina precursor solution with a solid content of 5-40 wt%; (2) mixing and reacting the alumina precursor solution with a phosphate at a temperature of 25-70°C and under stirring to obtain the phosphoaluminum binder.
[0056] The phosphate-aluminum binder used in the method disclosed in the present invention is prepared from low-cost aluminum salts and phosphates. The phosphate-aluminum binder has a small amount of free phosphate and a large amount of highly polymerized phosphate, and has good bonding properties. The stabilizer contained in the binder can effectively extend the service life of the phosphate-aluminum binder.
[0057] In a specific embodiment of the present disclosure, in step (1), the weight ratio of the aluminum source, water and stabilizer is 100:(50-800):(5-40), preferably 100:(100-750):(6-35), and the aluminum salt is calculated as aluminum oxide; in step (2), the weight ratio of the aluminum oxide precursor solution to the phosphate is 100:(50-200), preferably 100:(60-150), and the phosphate is calculated as phosphorus oxide. The dosage ratio of each material is appropriate within the above range, and a phosphorus aluminum binder with better bonding performance can be prepared.
[0058] According to the present disclosure, the porous silicon-aluminum composite material is obtained by hydrothermal crystallization of kaolin.
[0059] In a specific embodiment of the present disclosure, the porous silicon-aluminum composite material is prepared by a method comprising the following steps: (a) treating kaolin obtained by calcining kaolin with an inorganic acid at 80-95°C to obtain a first mixture; (b) mixing the first mixture, sodium silicate, a directing agent, and an alkaline solution to obtain a second mixture; wherein the second mixture has a composition with a weight ratio of (0.1-5) Na2O:Al2O3:(2-10)SiO2:(5-100)H2O; (c) subjecting the second mixture to a hydrothermal crystallization treatment, taking out a solid product, and obtaining the porous silicon-aluminum composite material.
[0060] According to the present disclosure, in step (b), the alkaline solution can be one or more of sodium hydroxide solution, ammonia water, potassium hydroxide, magnesium hydroxide and sodium carbonate.
[0061] The present disclosure does not specifically limit the method of removing the solid in step (c), for example, it may be a method such as suction filtration, centrifugal separation, filtration, etc. In a preferred specific embodiment, the solid product in step (c) is taken out and then washed and dried. According to the present disclosure, hydrothermal crystallization treatment is well known to those skilled in the art. In a preferred embodiment, the conditions of the hydrothermal crystallization treatment include: a temperature of 90-98°C and a time of 4-32h. The hydrothermal crystallization treatment can be carried out under the autogenous pressure of the system or under an applied pressure, preferably under the autogenous pressure of the system.
[0062] According to the present disclosure, in step (a), kaolin is calcined at 700-900°C for 1-3h to obtain the metakaolin. In a specific embodiment of the present disclosure, in step (a), the weight ratio of the inorganic acid to the metakaolin is (0.01-0.1):1, wherein the inorganic acid is H + The kaolin is measured on a dry basis; the weight ratio of the directing agent to the kaolin is (0.01-1.0):1, and the directing agent is measured on an oxide dry basis. According to the present disclosure, the inorganic acid may include but is not limited to hydrochloric acid, sulfuric acid, nitric acid, etc. The directing agent is a NaY molecular sieve synthesis directing agent well known to those skilled in the art. In one embodiment, the molar composition of the directing agent is: (10-17) SiO2: (0.7-1.3) Al2O3: (11-18) Na2O: (200-350) H2O. The directing agent can be synthesized according to conventional methods, such as according to the preparation methods of USP3574538, USP3639099, USP3671191, USP4166099, and EUP0435625.
[0063] In a specific embodiment of the present disclosure, the aluminum source is selected from one or more of aluminum nitrate, aluminum sulfate and aluminum chloride; the phosphate is diammonium hydrogen phosphate and / or ammonium dihydrogen phosphate; the stabilizer is selected from one or more of acetic acid, glycolic acid, oxalic acid, malonic acid, malic acid, tartaric acid, succinic acid, adipic acid, maleic acid, itaconic acid and citric acid, preferably acetic acid or citric acid.
[0064] A third aspect of the present disclosure provides a method for catalytic conversion of hydrocarbon oil, the method comprising: contacting the hydrocarbon oil with a catalyst for reaction, wherein the catalyst contains the catalytic composition provided by the first aspect of the present disclosure.
[0065] In a specific embodiment of the present disclosure, the catalyst is the catalyst composition provided in the first aspect of the present disclosure, and the reaction is a catalytic cracking reaction of hydrocarbon oil.
[0066] In a specific embodiment of the present disclosure, the catalyst is a mixture of the catalyst composition provided in the first aspect of the present disclosure and an optional main catalyst, and the reaction is a catalytic cracking reaction of hydrocarbon oil. According to the present disclosure, the main catalyst can be selected according to actual needs. In a specific embodiment of the present disclosure, the main catalyst can be selected from a catalytic cracking catalyst and / or a catalytic cracking catalyst.
[0067] In a specific embodiment of the present disclosure, the conditions for the catalytic cracking reaction of hydrocarbon oil include: a temperature of 400-700°C, preferably 450-550°C, a weight hourly space velocity of 8-120 hours -1 , preferably 8-80 hours -1 , the catalyst-oil weight ratio is 1-20, preferably 3-15. The catalytic composition provided by the present disclosure can be used in various existing catalytic cracking reactors, such as fixed bed reactors, fluidized bed reactors, riser reactors, multi-reaction zone reactors, etc.
[0068] According to the present disclosure, hydrocarbon oils may include, but are not limited to, wax oils, residual oils, and recycled oils.
[0069] The present disclosure is further illustrated below by way of examples, but the present disclosure is not limited thereby.
[0070] When the catalyst disclosed in the present invention is used for evaluating the performance of catalytic cracking reactions, an ACE device is used for evaluation.
[0071] The RIPP standard method described in the present disclosure can be specifically found in "Petrochemical Analysis Methods", edited by Yang Cuiding et al., 1990 edition.
[0072] Nitrogen adsorption method (GB / T5816-1995) for determination of specific surface area and pore volume: Nitrogen adsorption method (RIPP 151-90, "Determination of pore volume and pore size distribution of catalysts by nitrogen adsorption volumetric method", see Yang Cuiding et al., ed., Petrochemical Analysis Methods, Science Press, 1990) defines pores larger than 2 nm as mesopores, and the mesopore ratio is calculated as (V 总孔 -V 微孔 ) / V 总孔 ×100%.
[0073] The properties of some of the raw materials used in the examples are as follows:
[0074] Pseudo-boehmite is an industrial product produced by Shandong Aluminum Company, with a solid content of 60% by weight;
[0075] Alumina sol is an industrial product produced by Sinopec Catalyst Qilu Branch, with an Al2O3 content of 21.5% by weight;
[0076] The kaolin is kaolin specially used for catalytic cracking catalyst produced by Suzhou Kaolin Company, and has a solid content of 78% by weight.
[0077] Hydrochloric acid: chemically pure, concentration 36-38% by weight, produced by Beijing Chemical Plant.
[0078] MPZ molecular sieve: an industrial product produced by Sinopec Catalyst Qilu Branch, with a P2O5 content of 7.25% by weight, a Fe2O3 content of 1.95% by weight, and a crystallinity of 72%.
[0079] Sodium silicate solution: 20.65 wt% SiO2, 5.25 wt% Na2O, technical grade.
[0080] The average particle size of the aluminum-phosphorus binder was measured using a transmission electron microscope.
[0081] Preparation Examples 1-4 are preparation examples of the phosphorus aluminum binder disclosed in the present invention, and Preparation Example 5 is a preparation example of the porous silicon aluminum composite material disclosed in the present invention.
[0082] Preparation Example 1
[0083] (1) 0.56 kg of anhydrous aluminum sulfate, 0.25 kg of deionized water, and 0.05 kg of oxalic acid were mixed and stirred, and the mixture was heated to 70° C. and slurried for 30 minutes to obtain an aluminum oxide precursor solution having a solid content of 39 wt %;
[0084] (2) Control the temperature to 45°C and add 0.56 kg of ammonium dihydrogen phosphate to the alumina precursor solution prepared in step (1) under stirring, and then react at 45°C for 45 minutes until the mixture becomes a transparent colloid to obtain a phosphorus-aluminum binder P-1. The material ratio is shown in Table 1, and the nuclear magnetic resonance spectrum of the phosphorus-aluminum binder is shown in Figure 1 .
[0085] Preparation Example 2-4
[0086] The phosphate aluminum binder was prepared by the same method as in Preparation Example 1, except that different raw materials and their amounts were used. The specific material ratios are shown in Table 1.
[0087] Preparation Comparative Example 1
[0088] The inorganic binder containing phosphorus aluminum compound is prepared according to the method provided by patent ZL201110180891.X. The specific method is as follows:
[0089] At room temperature (25°C), 0.98 kg of pseudo-boehmite (containing 0.6 kg of Al2O3), 0.26 kg of rectorite (0.16 kg on a dry basis) and 0.44 kg of deionized water were mixed and slurried for 30 minutes. 2.01 kg of concentrated phosphoric acid (mass concentration 85%) was added to the slurry under stirring at a rate of 0.03 kg of phosphoric acid / min / kg of alumina source. The temperature was raised to 70°C and then reacted at this temperature for 45 minutes to obtain an inorganic binder DPAL-1 containing a phosphorus-aluminum compound. The NMR spectrum is shown in FIG. Figure 1 .
[0090] Depend on Figure 1 It can be seen that in the 31P nuclear magnetic resonance spectrum of the phosphorus aluminum binder, the peak area of the resonance signal with a chemical shift of 12±2ppm is defined as QP0 2 The peak area of the resonance signal with a chemical shift of 0±2ppm is defined as QP0 0 At the same phosphorus-aluminum ratio, the QP0 of the phosphorus-aluminum binder prepared in Preparation Example 1 is 2 / QP0 0 Compared with the QP0 of the aluminum-phosphorus binder prepared in Comparative Example 1 2 / QP0 0 Higher, indicating a higher degree of polymerization.
[0091] Table 1
[0092]
[0093]
[0094] Preparation Example 5
[0095] Preparation of the guiding agent: Take 245g of sodium silicate solution (containing 20.65 wt% SiO2 and 5.25 wt% Na2O), slowly add 118g of sodium aluminate solution (containing 3.22 wt% Al2O3 and 20.7 wt% Na2O) under rapid stirring, stir for 1 hour, and age at room temperature for 48 hours to obtain a guiding agent.
[0096] (1) 100 g (dry basis) of kaolin was calcined at 800° C. for 2 h to obtain metakaolin, and then treated with 2 L of 3 mol / L hydrochloric acid at 85° C. for 1 h under stirring, and then filtered and washed to obtain a first mixture;
[0097] (2) under stirring, the first mixture prepared in step (1) was mixed with 415 g of sodium silicate solution (containing 20.65 wt % SiO2 and 5.25 wt % Na2O), 60 g of directing agent, and 98 g of 5 wt % sodium hydroxide solution to obtain a second mixture having a composition of 0.69 Na2O:Al2O3:3.27SiO2:9.78H2O in a weight ratio;
[0098] (3) The second mixture was heated to 92°C and stirred at a constant temperature for hydrothermal crystallization for 20 hours. After the crystallization was completed, the crystallization tank was quenched, filtered, washed with water until the pH value of the washing liquid was less than 10, and dried at 120°C for 2 hours to obtain a porous silicon-aluminum composite material Y1, whose property parameters are shown in Table 2.
[0099] Preparation Example 6
[0100] (1) 100 g (dry basis) of kaolin was calcined at 900° C. for 2 h to obtain metakaolin, and then treated with 2 L of 3 mol / L hydrochloric acid at 90° C. for 1.5 h under stirring, and then filtered and washed to obtain a first mixture;
[0101] (2) under stirring, the metakaolin prepared in step (1) was mixed with 450 g of sodium silicate solution (containing 20.65 wt % SiO2 and 5.25 wt % Na2O), 60 g of a directing agent (the same directing agent as used in Preparation Example 5), and 120 g of a 5 wt % sodium hydroxide solution to obtain a second mixture having a composition of a weight ratio of 0.75 Na2O:Al2O3:3.43SiO2:10.81H2O;
[0102] (3) The second mixture was heated to 95°C and stirred at a constant temperature for hydrothermal crystallization for 28 hours. After the crystallization was completed, the crystallization tank was rapidly cooled, filtered, washed with water until the pH value of the washing liquid was less than 10, and dried at 120°C for 2 hours to obtain a porous silicon-aluminum composite material Y2.
[0103] Table 2
[0104]
[0105] ※ The meso-macro porosity refers to the proportion of the volume of meso-macro pores with a pore diameter of 2-50 nm to the total pore volume.
[0106] Examples 1-6 are examples of catalyst preparation.
[0107] Example 1
[0108] S1. Take MPZ molecular sieve, add decationized water and beat for 10 minutes, beat for 120 minutes to obtain molecular sieve slurry; add kaolin, porous silicon-aluminum composite material, aluminum sol and pseudo-boehmite to decationized water and beat for 20 minutes, add molecular sieve slurry under stirring, add hydrochloric acid to adjust the pH value of the slurry to 3.0, and then continue beating for 45 minutes to obtain the first slurry;
[0109] S2. Add the phosphorus aluminum binder P-1 to the first slurry prepared in step S1, stir for 5 minutes, spray dry the obtained slurry, and calcine the obtained microspheres at 500° C. for 2 hours to obtain a catalyst composition CAT-1, the proportion of which is shown in Table 3.
[0110] Embodiment 2-6
[0111] The catalytic composition was prepared in the same manner as in Example 1, except that different raw materials and their amounts were used. The specific ratios are shown in Table 3.
[0112] Comparative Example 1
[0113] Take MPZ molecular sieve, kaolin and aluminum stone, add decationized water and aluminum sol to slurry for 120 minutes, add hydrochloric acid to adjust the pH value of the slurry to 3.0, and then continue to slurry for 45 minutes, then add phosphate aluminum inorganic binder (DPAL-1), stir for 5 minutes, spray dry the obtained slurry to obtain microspheres, calcine the microspheres at 500°C for 1 hour to obtain DCAT-1, and its ratio is shown in Table 3.
[0114] Comparative Example 2
[0115] The catalytic composition was prepared in the same manner as in Example 1, except that the phosphorus-aluminum inorganic binder DPAL-1 was used instead of the phosphorus-aluminum binder P-1. The material proportions were as shown in Table 3.
[0116] Comparative Example 3
[0117] The catalytic composition was prepared in the same manner as in Example 1, except that the porous silicon-aluminum composite material was not added. The material proportions were as shown in Table 3.
[0118] Table 3
[0119]
[0120]
[0121] Test Case
[0122] The following examples take a fixed fluidized bed reactor as an example to illustrate the cracking reaction effect of the cracking catalyst provided by the present disclosure.
[0123] Catalytic cracking catalyst SLA and 30g CAT-1-6 and DCAT1-3 were aged for 17 hours at 800°C and 100% steam atmosphere. Different amounts of the aged catalysts were mixed with industrial balance agents (main properties are shown in Table 4), and the catalyst mixtures were loaded into the reactor of a small fixed fluidized bed reactor to catalytically crack the crude oil shown in Table 5. Table 6 shows the reaction conditions and reaction results.
[0124] Table 4 Main properties of industrial balancing agents
[0125]
[0126]
[0127] Table 5 Evaluation of the properties of the feedstock oil
[0128] <![CDATA[Density (20 °C), g / cm 3 > 0.92 Carbon residue, % (mass fraction) 4.81 Initial distillation point, ℃ 228.00 500℃ distillation amount, % (volume fraction) 44.50 538℃ distillation amount, % (volume fraction) 54.50 Asphaltene content, % (mass fraction) 1.73 Saturated hydrocarbon content, % (mass fraction) 58.17 Aromatic content, % (mass fraction) 29.01 Gum content, % (mass fraction) 11.10 Total nitrogen, mg / kg 594.30 Iron content, mg / kg 2.16 Sodium content, mg / kg 1.39 Nickel content, mg / kg, ≤10 6.44 Vanadium content, mg / kg, ≤10 8.91
[0129] Table 6 Evaluation results
[0130]
[0131]
[0132] It can be seen from Table 6 that, compared with the reference catalyst, the catalytic composition provided by the present disclosure can increase the yield of propylene, and the yield of light oil, i.e., the total yield of gasoline and liquefied gas, is high, the total liquid yield and conversion rate are high, the coke yield is lower, and the heavy oil cracking capacity and propylene selectivity are significantly improved.
[0133] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0134] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0135] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A catalytic composition for producing more low-carbon olefins and light oil, the catalytic composition comprising MFI molecular sieve, phosphorus aluminum binder, porous silicon aluminum composite material, other inorganic binders and clay; Based on the dry weight of the catalytic composition, the content of the MFI molecular sieve is 10-75% by weight, the content of the porous silicon-aluminum composite material is 1-30% by weight, the content of the phosphorus-aluminum binder calculated as oxide is 3-35% by weight, the content of the other inorganic binder calculated as oxide is 1-20% by weight, and the content of the clay is 0-60% by weight; The total weight of the phosphorus-aluminum binder is taken as the basis, and the phosphorus-aluminum binder contains 3-15 weight % of Al2O3, 15-40 weight % of P2O5 and 0.1-10 weight % of a stabilizer; the phosphorus-aluminum binder has a P / Al weight ratio of 1.6-6, a pH value of 0.5-2.5, and a QP0 2 / QP0 0 is 1-5, among which, QP0 2 Indicated by 31 The chemical shift of the phosphorus aluminum binder obtained by P nuclear magnetic resonance spectroscopy is 12±2ppm, QP0 0 Indicates the resonance signal peak area with a chemical shift of 0±2ppm; the average particle size of the phosphorus aluminum binder is 10-30nm; The porous silicon-aluminum composite material has a mass composition of (0.01-1) Na2O: Al2O3: (2-5) SiO2 and a specific surface area of 300-600m 2 / g, the total pore volume is 0.15-0.4mL / g, and the volume of medium and large pores with a pore diameter of 2-50nm accounts for 20-40% of the total pore volume.
2. The catalytic composition according to claim 1, wherein The phosphate aluminum binder contains 3-12 wt% Al2O3, 15-32 wt% P2O5 and 0.5-5 wt% stabilizer; the P / Al weight ratio of the phosphate aluminum binder is 1.7-5.8, the pH value is 0.5-2.5, QP0 2 / QP0 0 The solid content of the phosphorus aluminum binder is 15-50% by weight.
3. The catalytic composition according to claim 1, wherein Based on the dry weight of the catalytic composition, the content of the MFI molecular sieve is 15-65% by weight, the content of the porous silicon-aluminum composite material is 2-25% by weight, the content of the phosphorus-aluminum binder is 8-32% by weight, the content of the other inorganic binders is 2-20% by weight, and the content of the clay is 1-25% by weight.
4. The catalytic composition according to claim 1, wherein The other inorganic binder is one or more selected from pseudo-boehmite, acidified aluminum stone, aluminum sol, silica-alumina sol and silica sol; The clay is selected from one or more of kaolin, sepiolite, attapulgite, rectorite, montmorillonite and diatomaceous earth; The MFI molecular sieve is one or more of a hydrogen-type MFI molecular sieve, a phosphorus-containing MFI molecular sieve and a transition metal-containing MFI molecular sieve.
5. A method for preparing the catalytic composition according to any one of claims 1 to 4, the method comprising: S1, mixing the MFI molecular sieve, the porous silicon-aluminum composite material, the other inorganic binder, the clay and water, and controlling the pH value of the slurry to be greater than 2.5 to obtain a first slurry; S2. After mixing the first slurry with the phosphorus aluminum binder, spray drying and calcining are performed to obtain the catalytic composition.
6. The method according to claim 5, wherein: The aluminum-phosphorus binder is prepared by a method comprising the following steps: (1) mixing an aluminum source, water and a stabilizer at a temperature of 50-95° C. and stirring to obtain an aluminum oxide precursor solution having a solid content of 5-40% by weight; (2) Mixing and reacting the alumina precursor solution with phosphate at a temperature of 25-70° C. and under stirring conditions to obtain the phosphate-aluminum binder.
7. The method according to claim 6, wherein: In step (1), the weight ratio of the aluminum source, water and stabilizer is 100:(50-800):(5-40), preferably 100:(100-750):(6-35), and the aluminum salt is calculated as aluminum oxide; In step (2), the weight ratio of the aluminum oxide precursor solution to the phosphate is 100:(50-200), preferably 100:(60-150), and the phosphate is calculated as phosphorus oxide.
8. The method according to claim 5, wherein: The porous silicon-aluminum composite material is prepared by a method comprising the following steps: (a) treating metakaolin obtained by calcining kaolin with an inorganic acid at 80-95° C. to obtain a first mixture; (b) mixing the first mixture, sodium silicate, a directing agent and an alkaline solution to obtain a second mixture; wherein the second mixture has a composition of a weight ratio of (0.1-5) Na2O:Al2O3:(2-10)SiO2:(5-100)H2O; (c) After subjecting the second mixture to hydrothermal crystallization treatment, the solid product is taken out, filtered and washed to obtain the porous silicon-aluminum composite material.
9. The method according to claim 8, wherein: In step (a), the weight ratio of the inorganic acid to the metakaolin is (0.01-0.1):1, wherein the inorganic acid is H + The metakaolin is measured by dry basis weight; The weight ratio of the directing agent to the metakaolin is (0.01-1.0):1, and the directing agent is calculated on a dry basis of oxide.
10. The method according to claim 6, wherein: The aluminum source is selected from one or more of aluminum nitrate, aluminum sulfate and aluminum chloride; The phosphate is diammonium hydrogen phosphate and / or ammonium dihydrogen phosphate; The stabilizer is selected from one or more of acetic acid, glycolic acid, oxalic acid, malonic acid, malic acid, tartaric acid, succinic acid, adipic acid, maleic acid, itaconic acid and citric acid, preferably acetic acid or citric acid.
11. A method for catalytic conversion of hydrocarbon oil, the method comprising: The hydrocarbon oil is contacted with a catalyst for reaction, wherein the catalyst comprises the catalytic composition according to any one of claims 1 to 4.
12. The method according to claim 11, wherein: The reaction conditions include: temperature of 400-700°C, weight hourly space velocity of 8-120 hours -1 , the agent-oil weight ratio is 1-20.
Citation Information
Patent Citations
Inorganic binder containing phosphorus and aluminum compounds
CN102847547B
Cracking assistant for improving low-carbon olefin concentration
CN103007990A
Phosphorus-containing aluminum sol and preparation method thereof
CN107304332A
Catalytic cracking catalyst, preparation method thereof and hydrocarbon oil catalytic cracking method
CN112138712A
Assistant for increasing propylene yield and preparation method thereof, catalyst and application thereof, and hydrocarbon oil catalytic conversion method
CN116920923A